Family Support in Fulfilling Activities of Daily Living and the Level of Personal Hygiene - Bathing in Schizophrenia Patients - Lani, Tiara; Sitanggang, Yohana Agustina (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2024)
Aims: This research aims to analyze the relationship between Family Support in Fulfilling Activities of Daily Living and the level of Personal Hygiene - Bathing in schizophrenia patients. Methods: The population in this research consists of 88 families with schizophrenia patients, with a sample size of 47 respondents. The sampling technique used is random sampling, employing the Spearman's rho statistical test. This research was conducted from December 2022 to July 2023 in the village of Astambul, Banjar Regency, South Kalimantan Province, this research is an analytical research employing a cross-sectional design. Results: Based on the Spearman Rho test, the value of ρ is determined to be 0.005 (ρ ≥ 0.050). With a Spearman correlation value of 0.000, it indicates a positive correlation direction with a moderate strength. Conclusions: Emotional support and increased attention are crucial in supporting a more effective recovery process. The better the family support in fulfilling Activities of Daily Living (ADL) for schizophrenia patients, the higher the level of personal hygiene - bathing in schizophrenia patients in the Astambul village area, Banjar Regency.